Excitation Dynamics in Hetero‐bichromophoric Calixarene Systems. Issue 11 (15th March 2016) - Tosi, Irene; Segado Centellas, Mireia; Campioli, Elisa; Iagatti, Alessandro; Lapini, Andrea; Sissa, Cristina; Baldini, Laura; Cappelli, Chiara; Di Donato, Mariangela; Sansone, Francesco; Santoro, Fabrizio; Terenziani, Francesca
Abstract: In this work, the dynamics of electronic energy transfer (EET) in bichromophoric donor–acceptor systems, obtained by functionalizing a calix[4]arene scaffold with two dyes, was experimentally and theoretically characterized. The investigated compounds are highly versatile, due to the possibility of linking the dye molecules to the cone or partial cone structure of the calix[4]arene, which directs the two active units to the same or opposite side of the scaffold, respectively. The dynamics and efficiency of the EET process between the donor and acceptor units was investigated and discussed through a combined experimental and theoretical approach, involving ultrafast pump–probe spectroscopy and density functional theory based characterization of the energetic and spectroscopic properties of the system. Our results suggest that the external medium strongly determines the particular conformation adopted by the bichromophores, with a direct effect on the extent of excitonic coupling between the dyes and hence on the dynamics of the EET process itself. Abstract : Efficient energy transfer : The dynamics of electronic energy transfer in bichromophoric donor–acceptor systems obtained by functionalizing a calix[4]arene scaffold with two dyes is experimentally and theoretically characterized. Depending on the solvent, the equilibrium between an "open" or "closed" conformation of the system is differently shifted. Thus, variation in the kinetics of energy transfer from the donor to the acceptor is observed.